Impaired monocyte‐macrophage functions and defective toll‐like receptor signaling in hepatitis E virus‐infected pregnant women with acute liver failure. Issue 6 (28th October 2015) - Sehgal, Rashi; Patra, Sharda; David, Paul; Vyas, Ashish; Khanam, Arshi; Hissar, Syed; Gupta, Ekta; Kumar, Guresh; Kottilil, Shyam; Maiwall, Rakhi; Sarin, Shiv Kumar; Trehanpati, Nirupama
Abstract : Acute viral hepatitis resulting due to hepatitis E viral infection (AVH‐E) is often serious in pregnancy and could result in acute liver failure (ALF). The role of monocytes and macrophages (mono‐macs) in the pathogenesis of AVH‐E and development of ALF‐E in pregnancy is unclear. We investigated the functions of mono‐macs in pregnant (P), AVH‐E (n = 44), ALF‐E (n = 12), healthy controls (HC; n = 20) and compared with nonpregnant (NP) AVH‐E (n = 10), ALF‐E (n = 5), and HC (n = 10). We also recruited non‐hepatitis E virus‐related pregnant (P), ALF‐NE (n = 5) and non‐pregnant (NP), ALF‐NE (n = 12) patients with ALF. Mono‐macs, dendritic cell (DC) phenotypes, and Toll‐like receptor (TLR) expressions were studied by flow cytometry and reverse‐transcriptase polymerase chain reaction. Mono‐macs functionality was determined by analyzing their phagocytic activity and reactive oxygen species (ROS) generation by using flow cytometry. Frequency of mono‐macs and DCs was increased during HEV infection compared to HC ( P < 0.001). Macrophages were increased ( P < 0.002) in ALF‐E(P) compared to ALF‐NE(P). The macrophage phagocytic activity and Escherichia coli ‐induced ROS production was significantly impaired in ALF‐E(P) compared to AVH‐E(P) ( P < 0.001), ALF‐E(NP), and ALF‐NE(P) patients ( P < 0.02). TLR3 and TLR9 expression and downstream MYD88 signalling molecules IRF3 and IRF7 were significantly down‐regulated in ALF‐E(P) ( P < 0.00) compared to AVH‐E(P) and ALF‐NE(P). Conclusion: Functionality of mono‐macs is impaired in pregnant ALF‐E patients compared to AVH‐E(P). Reduced TLR3 and TLR7 expression and TLR downstream‐signaling molecules in pregnant ALF‐E patients suggests inadequate triggers for the innate immune responses contributing to development and severity of ALF‐E. Studies using TLR agonists to activate mono‐macs may be of use and in vitro studies should be undertaken using patient samples.(Hepatology 2015;62:1683–1696)